2013
DOI: 10.1186/1472-6920-13-107
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness training for stress management: a randomised controlled study of medical and psychology students

Abstract: BackgroundDistress and burnout among medical and psychology professionals are commonly reported and have implications for the quality of patient care delivered. Already in the course of university studies, medicine and psychology students report mental distress and low life satisfaction. There is a need for interventions that promote better coping skills in students in order to prevent distress and future burnout. This study examines the effect of a seven-week Mindfulness-Based Stress Reduction (MBSR) programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
227
3
23

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(284 citation statements)
references
References 48 publications
18
227
3
23
Order By: Relevance
“…Research has demonstrated some benefit to such programs in terms of mitigating medical student stress and distress [29,30]. Similarly, system-level interventions such as changing to a pass/fail grading system [26,3133], curricular restructuring [26,34], and introduction of mindfulness training [3540] have demonstrated improvements in student well-being. Each of these interventions appears to directly target some of the primary stressors noted by students in the present study (e.g., decreasing workload and academic pressure, limiting competition and promoting cooperation among students, teaching skills to enhance mental health), which may explain the positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated some benefit to such programs in terms of mitigating medical student stress and distress [29,30]. Similarly, system-level interventions such as changing to a pass/fail grading system [26,3133], curricular restructuring [26,34], and introduction of mindfulness training [3540] have demonstrated improvements in student well-being. Each of these interventions appears to directly target some of the primary stressors noted by students in the present study (e.g., decreasing workload and academic pressure, limiting competition and promoting cooperation among students, teaching skills to enhance mental health), which may explain the positive results.…”
Section: Discussionmentioning
confidence: 99%
“…As the outcome directions were the same for both genders, the differences in our results between men and women in the current study may be due to the low sample size. There are very few studies that have investigated the impact of gender on the effect of mindfulness-based intervention [27,40]. Future studies are needed to explore this issue in greater depth.…”
Section: Discussionmentioning
confidence: 99%
“…21 de Vibe et al also found significant stress reduction after mindfulness training in his sample of 144 undergraduate students from two universities. 22 Manoj and Rush, reviewed 17 studies on mindfulness-based stress reduction and its efficacy in decreasing stress in healthy individuals. In all studies they were able to find positive effects in psychological or physiological outcome measures related to stress.…”
Section: Discussionmentioning
confidence: 99%